Tafsir Maudhu'i Tentang Moderasi Beragama Dalam Era Media Sosial: Kajian Atas Ayat-Ayat Etika Komunikasi Dalam Al-Qur'an - Muhammad Hotibul Umam; Mohamad Hambali; Muhammad Fahrul Ihsan (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Amidst the flood of information on social media, which is rife with challenges such as disinformation, hate speech, and extremism, the need for a solid ethical foundation for communication is crucial to maintaining religious moderation (wasathiyyah). This study examines the ethics of communication in the Qur'an as a theological foundation for moderation in the digital space. Using the maudhu'i (thematic) interpretation method with a library research approach, verses from the Qur'an related to the ethics of communication were compiled and analyzed comprehensively. The results of the discussion show that the Qur'an offers a complete ethical system, which requires tabayyun (verification) and the delivery of qaul sadid (truthful speech). Thematic analysis of the concepts of qaul ma'rūf (good speech), qaul layyin (gentle speech), and the prohibition of ghibah and su'u al-zhan (bad assumptions) confirms that moderation in speech is an intrinsic value in Islam. In conclusion, the internalization of Qur'anic communication ethics not only serves as a moral guide but also as a vital epistemological instrument to stem radical narratives and achieve harmony in the digital age. Keywords: Tafsir Maudhu'i, Religious Moderation, Social Media, Communication Ethics, Al-Qur'an Abstrak Di tengah arus informasi media sosial yang sarat dengan tantangan disinformasi, ujaran kebencian, dan ekstremisme, kebutuhan akan landasan etika komunikasi yang kokoh menjadi krusial untuk menjaga moderasi beragama (wasathiyyah). Penelitian ini mengkaji etika komunikasi dalam Al-Qur'an sebagai fondasi teologis untuk moderasi di ruang digital. Menggunakan metode tafsir maudhu'i (tematik) dengan pendekatan studi pustaka (library research), ayat-ayat Al-Qur'an yang berkaitan dengan etika komunikasi dihimpun dan dianalisis secara komprehensif. Hasil pembahasan menunjukkan bahwa Al-Qur'an menawarkan sebuah sistem etika yang utuh, yang menuntut adanya tabayyun (verifikasi) dan penyampaian qaul sadid (perkataan yang benar). Analisis tematik pada konsep qaul ma'rūf (perkataan baik), qaul layyin (lemah lembut), serta larangan ghibah dan su'u al-zhan (prasangka buruk) menegaskan bahwa moderasi dalam bertutur adalah nilai intrinsik dalam Islam. Kesimpulannya, internalisasi etika komunikasi Qur'ani ini tidak hanya berfungsi sebagai panduan moral, tetapi juga sebagai instrumen epistemologis yang vital untuk membendung narasi radikal dan mewujudkan harmoni di era digital. Kata Kunci: Tafsir Maudhu'i, Moderasi Beragama, Media Sosial, Etika Komunikasi, Al-Qur'an